O método clínico na medicina antroposófica e a clínica foniática: o homem em sua complexidade - Fernandes, Mauro Domingues (2006)
This work aims at investigating the clinic method in anthroposophic medicine, identifying the contributions of its approach for the comprehension oh hearing and language in phoniatric practice, and identifying possible outcomes in the construction of therapeutic paths on language disorders. The investigation presents a case study design as it is configured by the analysis of a limited set of situations in their several relationships relative to a specific process: a case in which the clinic method in anthroposophic medicine has been applied, having relative requirements for hearing and language disorders, creating the possibility of understanding the diagnostic steps inherent to this methodology, its different integrated qualitative perspectives in dialogue with the quantitative data, and the therapeutic strategies in varied scopes which arise during the conduction of such process, making up a clinic planning. This is one of the challenges that anthroposophic medicine must face in this practice from its epistemologic bases, trying to clasp the mankind in its complexity in physical, animical and spiritual perspective in their sensitivy and super-sensitivy reality, thus, in qualitative-quantitative approach. It was introduced in Brazil in the 1960s, having been reckoned as a medical practice by the Conselho Federal de Medicina in 1993. It has its epistemological foundations in the Anthroposophy, which is a scientic-philosophical movement begun in the early 20th century in Switzerland and Germany by the Austrian epistemological philosopher and educator Rudolf Steiner (1861 1925). Worldwidely, the anthroposophic medicine was begun by the Dutch doctor Ita Wegman in Switzerland between 1920 and 1924, having a progressive spread, initially in Europe, and afterwards, during the 20th century, towards the other continents. The unfoldings of this clinic method have been observed in the phonological practice, deepening the diagnostical possibilities with the enhancement of the therapeutical strategies focused on a binomial phoniatry-phonoaudiology, including other health and education professionals to form a community. The contributions for the health sciences in the present times, before their dilemmas and perspectives, have been observed, including epistemological reflexions, the humanization of procedures, researches, and the deepening in the use of natural therapeutics, including medicinal ones and salutogenical emphasis in its practice